تطوير مقرّر إلكتروني بوسيلة كانفا لتعليم قواعد الصرف في مدرسة الاتحاد الثانوية الإسلامية فونجوكوسومو مالانج - Sholihah, Al Mar'atus; Hamid, M Abdul (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
ABSTRACT In this research and development, the researcher has the initiative to develop an electronic module in Qowaid shorof learning for students in class XI of Madrasah Aliyah Al-Ittihad Poncokusumo Malang. This research and development aims (1) to find out the procedure for developing electronic module using Canva in Qowaid learning at Madrasah Aliyah Al-Ittihad Poncokusumo Malang, and (2) to find out the effectiveness of using electronic module with Canva in Qowaid learning at Madrasah Aliyah Al-Ittihad Poncokusumo Malang. The development model used was the ADDIE model, which had five stages of research and development. The result shows: 1) Development, it considers the Arabic language module used then develops them into an electronic module that follows the latest technology and innovations. 2) The result of the material expert validation test on the electronic module is 83%, and from the media expert validation is 92%. Based on these data, it is known that this electronic module is appropriate for students. From the value of the N-Gain calculation results, the effectiveness level of electronic module produces N value of 84.5 or a percentage of 85%. It means that the module is effective to implement. ملخص في هذا البحث التطويري، أخذت الباحثة زمام المبادرة لتطوير مقرّر إلكتروني في تعليم قواعد الصرف لطلاب الصف الحادي عشر في مدرسة الاتحاد الثانوية الإسلامية فونجوكوسومو مالانج. أهداف هذا البحث التطويري هي ؛ (1) لمعرفة إجراء تطوير مقرّر إلكتروني بوسيلة كانفا لتعليم قواعد الصرف في مدرسة الاتحاد الثانوية الإسلامية فونجوكوسومو مالانج. (2) لمعرفة فعالية استخدام مقرّر إلكتروني بوسيلة كانفا لتعليم قواعد الصرف في مدرسة الاتحاد الثانوية الإسلامية فونجوكوسومو مالانج. يستخدم هذا البحث منهج البحث التطويري. نموذج التطوير المستخدم هو نموذج ADDIE الذي يحتوي على خمسة مراحل من البحث التطويري. وتتمثل نتائج هذا البحث فيما يلي: 1) التطوير، أي من خلال النظر في الوحدة العربية المستخدمة ثم تطويرها إلى مقرّر إلكتروني تتوافق مع أحدث التقنيات والابتكارات. 2) تبلغ قيمة التحقق من صحة خبير المادة في مقرّر إلكتروني 83٪ ومن التحقق من صحة خبير الوسيلة 92٪. بناء على هذه البيانات، من المعروف أن هذه المقرّر إلكتروني قابلة للتنفيذ للطلاب. من قيمة نتيجة حساب N-Gain، ينتج معدل فعالية المقرّر إلكتروني قيمة N تبلغ 84.5 أو نسبة مئوية قدرها 85٪ أن مقرّر إلكتروني فعالة.